CLINICAL AND BIOCHEMICAL PROFILE OF STEROID-INDUCED DIABETES - Rao N, Karthik; Patil, Navin; Vidyasagar, Sudha; Rau, N R; Holla, Avinash Manjunath; Avinash, A (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To study the clinical and biochemical profile of patients who develop steroid-induced diabetes (SID) and its predisposing factors. Methods: Non-diabetic patients aged â‰¥18 years started on steroids were considered eligible for the study. In every case after detailed examination, fasting plasma glucose (FPG), post-prandial plasma glucose (PPG), glycated hemoglobin, fasting insulin were measured prior to starting steroids and was repeated in 1 week (day 3/4) after starting steroid according to standard guidelines. FPG and PPG were repeated periodically during follow-up of the patients. The utility of Indian diabetic risk score (IDRS) score in predicting the risk for SID was also assessed. st Result: Steroid-induced diabetes was found to be more in females than in males. IDRS is not useful in predicting the risk factors of SID. 97% of patients had an elevation of post-prandial sugars with or without fasting hyperglycemia, but only 3% of patients had isolated elevation of fasting blood sugar. 84% of patients developed SID during the 1 week of therapy. 33% of the cases SID persisted even after 1 month of stopping steroids and on a minimal dosage of steroids. st Conclusion: Unlike type 2 diabetes, there were no significant risk factors such as age, family history of diabetes to develop SID and IDRS may not be a sensitive tool for predicting risk factors of SID. Monitoring of post-prandial sugars as compared to fasting sugars is essential for the screening of SID. Cumulative dose of steroid may not be important to precipitate steroid diabetes. Keywords: Glucocorticoids, Diabetes, Post-prandial glucose, Indian Diabetic Risk Score.